2011
DOI: 10.3109/00498254.2011.603385
|View full text |Cite
|
Sign up to set email alerts
|

In vitrometabolic interactions between black cohosh (Cimicifuga racemosa) and tamoxifen via inhibition of cytochromes P450 2D6 and 3A4

Abstract: Women who experience hot flashes as a side effect of tamoxifen therapy often try botanical remedies such as black cohosh to alleviate these symptoms. Since pharmacological activity of tamoxifen is dependent on the metabolic conversion into active metabolites by the action of cytochromes P450 2D6 and 3A4, the objective of this study was to evaluate whether black cohosh extracts can inhibit formation of active tamoxifen metabolites and possibly reduce its clinical efficacy.At 50 µg/ml, a 75% ethanolic extract of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…For example, we found that protopine and allocryptopine are potent inhibitors of CYP2D6 and may be involved in potential interactions of black cohosh with drugs metabolized by this isoform such as tamoxifen [75]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, we found that protopine and allocryptopine are potent inhibitors of CYP2D6 and may be involved in potential interactions of black cohosh with drugs metabolized by this isoform such as tamoxifen [75]. …”
Section: Resultsmentioning
confidence: 99%
“…Although several studies reported herbal supplements to be safe, their potential for interactions with other drugs were not discussed. For example, black cohosh (Li et al, ), chasteberry (Ho, Singh, Holloway, & Crankshaw, ), chamomile (Ganzera, Schneider, & Stuppner, ), and rhodiola (Hellum et al, ) are known to modulate the actions of cytochrome P450 enzymes and may increase the toxicity or decrease therapeutic effects of substrate drugs (Gurley, Fifer, & Gardner, ) including many used in cancer treatment, such as cyclosporine (Sridharan & Sivaramakrishnan, ) and most of the tyrosine kinase inhibitors (Gay, Toulet, & Le Corre, ). Even though the clinical significance of these interactions is yet to be determined, the potential exists and therefore should be given due consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evaluation of the data using Dixon plots suggested that the commercial preparations of SJW and BC used in this study inhibited the bioactivation of tamoxifen (mediated by CYP2D6, 3A4 and flavin‐containing monooxygenase) predominately by a non‐competitive mechanism, and that BC is a much stronger inhibitor of tamoxifen metabolism than SJW (Table ). Recently, it has been shown that at 50 μg/ml, a 75% ethanolic extract of BC inhibited the formation of 4‐hydroxytamoxifen by 66.3% and eight triterpenes identified did so via competitive inhibition of CYP3A4, with IC50 values of 5.1 µ m or less . From inhibition reactions of tamoxifen with GRE, the Dixon plot suggests that significant contributions to the overall inhibition were being made by multiple mechanisms, thus resulting in an indeterminate or mixed‐type mechanism.…”
Section: Discussionmentioning
confidence: 99%